THE DEVELOPMENT OF STUDENT WORKSHEET BASES GOOGLE FORM TO IMPROVE THE FIFTH GRADE ELEMENTARY SCHOOL CIENCE CONCEPTS UNDERSTANDING - Namira Aulia Azzahro; Jajang Bayu Kelana (Sekolah Pascasarjana UPI, 2022)
The problem on the ground is lack of understanding of students' science concepts. This condition can occur because students are less motivated in learning and lack of student participation in class. So this study developed a student worksheet based on google form. This study aims to produce an interactive student worksheet product so that it can improve students' understanding of science concepts. This study uses research and development (rd) method of borg and gall model. Sample in this study were students of class v at private mi in padalarang area. Results of student worksheet development deserve to be tested. This can be seen from results of validation carried out by media experts who got 89%, material experts got 92%, and expert practitioners got 83.75%, three validations were categorized as very good. Learning to use this student worksheet runs smoothly. This can be seen from student responses, in limited trial obtaining 86%, while in wide trial obtaining 87%, both trials are categorized as very good. This is evidence that there is an increase in students' understanding of science concepts, in limited trial obtaining 70.81 and broad trial obtaining 76.95. Thus, student worksheet based on google form can improve understanding of science concepts for fifth grade elementary school students.